Kebebasan Beragama di Indonesia dalam Terang Pemikiran Barcuh de Spinoza - Sirilus Yekrianus (Parahyangan Catholic University, 2021)
This paper pays attention to the issue of religious freedom in Indonesia. Freedom of religion is one of the individual rights of every person. People are free to choose religion according to their minds. By reason, it means that humans recognize the values that are sparked in a religion. The duty of the state is to guarantee religious freedom. In the Indonesian context, freedom of religion is guaranteed in the legal basis contained in the 1945 Constitution. However, it is inevitable that this kind of freedom is also subject to discriminatory treatment. To underline this, Spinoza, a philosopher who greatly respected reason, explained the importance of religious freedom as an individual choice. Freedom of religion according to him should not be restrained by any authority. This paper was written using the literature method which tries to confront Spinoza's thoughts on religious freedom with the issue of religious freedom in Indonesia.